Multidirectional myocardial function in bicuspid aortic valve stenosis patients: a three-dimensional speckle tracking analysis - Deng, Wenhui; Tan, Yuting; Shi, Jiawei; He, Shukun; Liu, Tianshu; Wu, Wenqian; Li, Yuman; Yang, Yali; Zhang, Li; Xie, Mingxing; Wang, Jing (Frontiers in Cardiovascular Medicine, 2024)
Purpose The impact of aortic stenosis (AS) severity on multidirectional myocardial function in patients with bicuspid aortic valve (BAV) remains unclear, despite the recognized presence of early left ventricular longitudinal myocardial dysfunction in BAV patients with normal valve function. The aim of the study was to evaluate the multidirectional myocardial functions of BAV patients. Methods A total of 86 BAV patients (age 46.71 ± 13.62 years, 69.4% men) with normally functioning (BAV-nf), mild AS, moderate AS, and severe AS with preserved left ventricular ejection fraction (LVEF ≥ 52%) were included. 30 healthy volunteers were recruited as the control group. Multidirectional strain and volume analysis were performed by three-dimensional speckle tracking echocardiography(3D-STE). Results Global longitudinal strain (GLS), and global radial strain (GRS) were reduced in BAV-nf patients compared with the controls. With each categorical of AS severity from BAV-nf to severe AS, there was an associated progressive impairment of GLS and GRS (all P < 0.001). Global circumferential strain (GCS) did not show a significant decrease from BAV-nf to mild AS but began to decrease from moderate AS. Multiple linear regressions indicated that indexed aortic valve area (AVA/BSA), as a measure of AS severity, was an independent determinant of GLS, GCS and GRS. Conclusions Left ventricular longitudinal myocardial reduction is observed even in patients with well-functioning bicuspid aortic valves. With each categorical increase in the grade of AS severity from normally functioning to severe aortic stenosis, there was an associated progressive impairment of longitudinal myocardial function. Furthermore, circumferential myocardial function was starting damaged from moderate AS. AVA/BSA was independently associated with multidirectional myocardial function injuries.